2014
DOI: 10.1016/j.ijid.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum in patients with AIDS: a case report and literature review

Abstract: In HIV-infected patients, Pneumocystis jirovecii pneumonia can occasionally present as pneumomediastinum. In such cases, adequate appropriate antimicrobial therapy is needed due to the high mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…On the basis of aging lung changes, broncho-pulmonary infection is also a risk factor for we have found several papers that have also reported pneumomediastinum in conjunction with other pulmonary infections. Pneumomediastinum can be found in patients with AIDS presenting with community-acquired pneumonia due to Pneumocystis jirovecii [ 7 ]. Separately, Hasegawa et al[ 8 ] showed two children infected with the flu virus of H1N1 who developed SPM.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of aging lung changes, broncho-pulmonary infection is also a risk factor for we have found several papers that have also reported pneumomediastinum in conjunction with other pulmonary infections. Pneumomediastinum can be found in patients with AIDS presenting with community-acquired pneumonia due to Pneumocystis jirovecii [ 7 ]. Separately, Hasegawa et al[ 8 ] showed two children infected with the flu virus of H1N1 who developed SPM.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pneumomediastinum in PCP is thought to be 0.4-3.3%. 4 The abrupt change in transalveolar pressure that leads to spontaneous pneumomediastinum was first described in 1939 by Macklin who proposed that an abrupt change in pressure due to coughing or straining could cause alveolar rupture and tracking of air along the interstitial sheaths toward the mediastinum. 5 In general, alveolar rupture is reported to be the cause of spontaneous pneumomediastinum in over 95% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumomediastinum is the presence of extra-alveolar air in the mediastinum, which is believed to arise from free air leaking from ruptured alveoli. It was described as an uncommon complication of opportunistic infections in HIV-infected patients [ 13 , 14 ]. However, 24.4 % patients in our study developed pneumomediastinum.…”
Section: Discussionmentioning
confidence: 99%